O indianismo e o problema da identidade nacional em A lágrima de um Caeté, de Nísia Floresta - Lima, Stélio Torquato (2008)
The Romantic period has figured itself in Brazil as a relevant stage of the construction process of our national identity. Soon after Independence, Romanticism established in our country, thus it was characterized by our writers’ effort in order to create symbols by means of which we could be recognized by other nations. It is in this perspective that Nísia Floresta (1810-1885), who was an authoress of Rio Grande do Norte state, developed an interesting reflection about Brazilian identity in A lágrima de um caeté (A caeté’s tear), a long poem written in 1849 by which Nísia Floresta expressed her republican aspiration. By doing so, she shows sympathy for the Praieira Revolt, at the same time she shows imperial troops as antagonists of her narrative, Nísia Floresta takes advantage of Indianism in the above-mentioned work as a structural pattern of a discourse through which she expresses her political position. In spite of that, it is necessary to point out that the poem in focus is also marked by disagreements between Nisia Floresta’s humanitarian intentions and the place from where she used to emit her speech, considering her condition as a dominant class representative and as an intellectual from a peripheral nation as well. In this context, this thesis is developed having as its analysis horizon the hypothesis that the representation of our Indians in A lágrima de um caeté comes to agree with the Brazilian elite’s majority point of view about the national identity question. In the analysis of national identity question in A lágrima de um caeté, we are based on a nation understanding as a discursive and ideological construction, the same comprehension defended by theorists such as Eric Hobsbawn, Bendict Anderson and Homi Bhabha. On the other hand, Mikhail Bakhtin’s theoretical postulations, emphasizing the dialogism and polyphony concepts, have allowed us to understand how the relation among the nisian poem’s voices in conflict reflects the social and historical contingencies that obstruct, in the first half of 19th century, the construction of a national identity that could range Brazilian cultural diversity as a whole. It is in this perspective that we demonstrate in our thesis how A lágrima de um caeté and its textual attributes have been organized as an esthetical representation of our national identity.